Case Report: Desmoid tumor response to magnetic resonance-guided high intensity focused ultrasound over 4 years - Yeo, Sin Yuin; Bratke, Grischa; Knöll, Peter; Walter, Sebastian Gottfried; Maintz, David; Grüll, Holger (Frontiers in Oncology, 2023)
Desmoid tumors are a rare form of cancer, which show locally aggressive invasion of surrounding tissues and may occur anywhere in the body. Treatment options comprise conservative watch and wait strategies as tumors may show spontaneous regression as well as surgical resection, radiation therapy, nonsteroidal anti-inflammatory drugs (NSAID), chemotherapy, or local thermoablative approaches for progressive disease. The latter comprises cryotherapy, radiofrequency, microwave ablation, or thermal ablation with high intensity focused ultrasound (HIFU) as the only entirely non-invasive option. This report presents a case where a desmoid tumor at the left dorsal humerus was 2 times surgically resected and, after recurrence, thermally ablated with HIFU under magnetic resonance image-guidance (MR-HIFU). In our report, we analyze tumor volume and/or pain score during standard of care (2 years) and after HIFU treatment over a 4-year follow-up period. Results showed MR-HIFU treatment led to complete tumor remission and pain response.